Komunikasi Interpersonal Penyandang Tunadaksa dalam Menghadapi Stigma Sosial Masyarakat di Kota Palembang - M Nur Qudri; Kun Budianto; Badarudin Azarkasyi (LPPM Universitas HKBP Nommensen, 2025)
People with physical disabilities are a group of people with disabilities who often face various social barriers, one of which is negative stigma from society. This stigma appears in the form of stereotypes, discrimination, and demeaning treatment that can affect their self-confidence and ability to interact socially. This condition shows that interpersonal communication plays a crucial role in helping people with physical disabilities build better social relationships and reduce the stigma that develops in society. This study aims to analyze how interpersonal communication is carried out by people with physical disabilities in dealing with social stigma in Palembang City and identify communication strategies used to overcome this stigma. This study uses a qualitative approach with descriptive methods. Data were obtained through observation, in-depth interviews, and documentation of six informants with physical disabilities in Palembang City. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. This study uses the Fundamental Interpersonal Relations Orientation theory which emphasizes three basic needs for interpersonal relationships: inclusion, control, and affection. The results show that interpersonal communication of people with physical disabilities in dealing with social stigma is carried out through efforts to build social involvement, demonstrate independence in interactions, and create positive emotional relationships with the social environment. Communication strategies used include self-disclosure, participation in social activities, and building a positive self-image to demonstrate ability and independence. These strategies can gradually reduce social stigma and increase public acceptance of people with disabilities..